Effects of Biochar on the Growth and Development of Tomato Seedlings and on the Response of Tomato Plants to the Infection of Systemic Viral Agents - Luigi, Marta; Manglli, Ariana; Dragone, Immacolata; Antonelli, Maria Grazia; Contarini, Mario; Speranza, Stefano; Bertin, Sabrina; Tiberini, Antonio; Gentili, Andrea; Varvaro, Leonardo; Tomassoli, Laura; Faggioli, Francesco (Frontiers in Microbiology, 2022)
Biochar is composed mainly of aromatic molecules, but its agronomic value is hard to evaluate and difficult to predict due to its great variable characteristics depending on the type of starting biomass and the conditions of pyrolysis. Anyway it could be used as soil amendment because it increases the soil fertility of acidic soils, the agricultural productivity and seems to provide protection against some foliar and soil-borne diseases. In this paper the effects of biochar, obtained from olive pruning, have been evaluated on tomato seedlings growing and on their response to systemic agents’ infection alone or added with advantageous microorganisms (Bacillus spp. and Trichoderma spp.). First experimental data showed that biochar seems to promote the development of the tomato seedlings especially at concentrations ranging from 1- 20% (w/w with peat) without showing any antimicrobial effects on the beneficial soil bacteria at the tomato rhizosphere level, indeed, their growth seemed to be improved. Thus, those concentrations were used in growing tomato plants experimentally infected with tomato spotted wilt virus (TSWV) and potato spindle tuber viroid (PSTVd). The biochar effect was estimated evaluating three parameters: symptoms expression, number of infected plants, and pathogen quantification using RT-qPCR technique and ∆∆Ct analysis. At the concentration of 10 - 15 % and in combination with Trichoderma spp. biochar highlights a positive activity addressed to the plant pathogen management. It can sensibly reduce the replication of PSTVd and the symptoms’ expression even if it is not able to block the starting of infection. Instead on TSWV, the use of biochar, not only reduce the replication of the virus but seems to help the plants to block the infection. As it is well known, for systemic viral agents, such as PSTVd and TSWV, there are no curative control methods and therefore the use of prevention means, as can be assumed the use biochar for example in the nursery specialised in horticultural crops, can be of great help. These results can be an encouraging start point for trying to manage systemic infections for vegetable plants using complex biochar formulates.